2021
DOI: 10.1007/s10393-021-01531-1
|View full text |Cite
|
Sign up to set email alerts
|

Active Forest Management Reduces Blacklegged Tick and Tick-Borne Pathogen Exposure Risk

Abstract: In the northeastern USA, active forest management can include timber harvests designed to meet silvicultural objectives (i.e., harvesting trees that meet certain maturity, height, age, or quality criteria). Timber harvesting is an important tool in enhancing regeneration and maintaining forest health. It also has considerable potential to influence transmission dynamics of tick-borne pathogens, which are deeply embedded in the forest ecosystem. We conducted a 2-year study to test the hypotheses that recent tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Contrary to our predictions, there was no observed difference in infection probability among forest types. However, this result runs parallel to findings by Conte et al (2021) who reported that timber harvesting affected density of host-seeking nymphs, but not nymphal infection prevalence. Although I. scapularis distribution has been shown to be spatially auto-correlated at the national and state scale, there appears to be high variability in tick distribution at finer scales (Pardanani and Mather 2004).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to our predictions, there was no observed difference in infection probability among forest types. However, this result runs parallel to findings by Conte et al (2021) who reported that timber harvesting affected density of host-seeking nymphs, but not nymphal infection prevalence. Although I. scapularis distribution has been shown to be spatially auto-correlated at the national and state scale, there appears to be high variability in tick distribution at finer scales (Pardanani and Mather 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Forest management effectively modifies the amount and availability of resources and habitat features which subsequently affects wildlife community richness and composition (Fisher and Wilkinson 2005; Gasperini et al 2016; Sozio and Mortelliti 2016) as well as intraspecific behavioral traits (Mortelliti and Brehm 2020). In vector–pathogen systems, forest management practices directly impact disease prevalence by altering pathogen and vector habitat quality, host abundance, and movement patterns (Ehrmann et al 2018; Conte et al 2021). Forest management practices including invasive plant removal, prescribed burns, and timber harvesting alter critical habitat features and have been strongly linked to B. burgdorferi prevalence in vertebrate hosts (Stafford et al 1998; Williams and Ward 2010; Conte et al 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In temperate regions, a global analysis revealed that outbreaks of zoonotic and vector-borne diseases were linked with increases in forest cover (Morand & Lajaunie, 2021). Studies in small scales presented contradictory results, showing no effect (Conte et al, 2021), increased (Dalgleish & Swihart, 2012) or even reduced risk (Morlando et al, 2012). Yet, these studies did not evaluate the increment of forest cover per se, but compared areas restored by specific managements with unrestored areas.…”
Section: Mosquito-borne Diseases (Diseases Transmitted By Aedes Anoph...mentioning
confidence: 99%
“…Yet, these studies did not evaluate the increment of forest cover per se, but compared areas restored by specific managements with unrestored areas. The findings were: restoration through timber harvest presented no effect on tick‐borne disease risk (Conte et al, 2021), reintroduction of blight‐resistant chestnut increased zoonotic risk (Dalgleish & Swihart, 2012) and restoration through active management and through removal of invasive species presented decreases in Lyme disease (Morlando et al, 2012) and ehrlichiosis (Allan et al, 2010) risk. In addition, rodents in young forests were more likely to be infected with hantavirus than in mature forests (Voutilainen et al, 2012), suggesting a potential time lag in response, where zoonotic risks could be elevated initially before eventually decreasing.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%